Single active element based electronically controllable grounded inductance simulator - Siriphot, David; Maneewan, Suwat; Jaikla, Winai (My University, 2013)
This article presents grounded inductance simulator using single current controlled current follower transconductance amplifier (CCCFTA) as active element. The simulated inductance value can be controlled electronically by adjusting the bias current of the CCCFTA. The grounded inductance simulator comprises one CCCFTA and one grounded capacitor without any external resistors and component matching requirements. The circuit performances are depicted through PSpice simulations, they show good agreement to theoretical anticipation. An application as second-order low-pass filter is included to confirm the usability of proposed circuit. It is very suitable to realize the proposed filter in monolithic chip to use in biomedical signal processing. © 2013 IEEE.
Keywords: CCCFTA; CMOS; Inductance Simulator; Integrated Circuit